GAMBARAN ILEUS OBSTRUKTIF PADA ANAK DI RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE JANUARI 2012 – DESEMBER 2014 - Novita Sari; Ismar "; Elda Nazriati (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTObstructive ileus is a condition that causes the intestinal contents cannot pass through the intestinal lumen as a result of blockage or mechanical barriers. Obstructive ileus is an emergency in surgical and also a case which frequently happen to children including newborns. The research using a retrospective descriptive method regarding obstructive ileus overview of children in Arifin Achmad hospital of Riau province period of January 2012– December 2014 and the data is from medical records in Medical Record Installation of Arifin Achmad Hospital Pekanbaru. In the research, 123 obstructive ileus patients were found in children. Based on age, most of them were in the age group of >28 days-12 months with 37,4%, most numerous gender was male with 74,8% , there were four most common causes of obstructive ileus, they were Hirschsprung with 27,6%, adhesion with 22%, atresia ani with 21,2% and intussusception with 17,1%, most of the type of obstruction is simple obstruction with 87%, most of the obstruction position is low-level obstruction with 75,6%, the most clinical symptoms were abdominal distention with 78,9%, obstipation with 65,9%, vomiting with 61%, abdominal pain with 19,5%. Most of the obstructive ileus patients 67,5% returned home with the status/condition in a state of improvement.Keywords: obstructive ileus, obstructive ileus etiology, patient overview.